Co‐administration of tacrolimus and low molecular weight heparin in patients with a history of implantation failure and elevated peripheral blood natural killer cell proportion. Issue 2 (27th November 2022) - Shen, Ping; Zhang, Tao; Han, Ru; Xie, Huixia; Lv, Qun
Abstract: Aim: To investigate the therapeutic effect of co‐administration of tacrolimus (TAC) and low‐molecular‐weight heparin (LMWH) or LMWH only on pregnancy outcomes in the female with a history of implantation failure and elevated peripheral blood natural killer (pNK) cell proportion in frozen‐thawed embryo transfer cycles. Methods: To evaluate the pregnancy parameters for 249 patients with ≥2 implantation failures and pNK cell proportion ≥12% by analyzing a retrospective observational cohort study. Sixty patients had received the co‐administration TAC and LMWH (TAC & LMWH group), 85 others had only taken LMWH (LWMH group), and the rest did not take any particular drugs (control group). Results: The experimental finding indicated that the TAC & LMWH group and the LMWH group showed higher clinical pregnancy rates than the control group ( p  < 0.05), and TAC & LMWH group had a much higher live birth rate. According to the binary logistic regression analysis, the combination of TAC and LMWH was conducive to clinical pregnancy and live birth rate and reduced the possibility of miscarriage. It would not affect the result of spontaneous abortion and live birth, although the LMWH was only beneficial to clinical pregnancy. In addition, these findings were similar for these three groups' obstetrical and neonatal outcomes. Conclusions: The combination of TAC and LMWH can improve clinical pregnancy and live birth rates and reduce the risk of spontaneous miscarriage in patients with a history of implantation failure and elevated pNK ratio. LMWH is also beneficial to clinical pregnancy.